Compression mechanisms in the plasma focus pinch - Lee, S.; Saw, S. H.; Jalil, Ali (AIP Publishing, 2017)
The compression of the plasma focus pinch is a dynamic process, governed by the electrodynamics of pinch elongation and opposed by the negative rate of change of current dI/dt associated with the current dip. The compressibility of the plasma is influenced by the thermodynamics primarily the specific heat ratio; with greater compressibility as the specific heat ratio γ reduces with increasing degree of freedom f of the plasma ensemble due to ionization energy for the higher Z (atomic number) gases. The most drastic compression occurs when the emitted radiation of a high-Z plasma dominates the dynamics leading in extreme cases to radiative collapse which is terminated only when the compressed density is sufficiently high for the inevitable self-absorption of radiation to occur. We discuss the central pinch equation which contains the basic electrodynamic terms with built-in thermodynamic factors and a dQ/dt term; with Q made up of a Joule heat component and absorption-corrected radiative terms. Deuterium is considered as a thermodynamic reference (fully ionized perfect gas with f = 3) as well as a zero-radiation reference (bremsstrahlung only; with radiation power negligible compared with electrodynamic power). Higher Z gases are then considered and regimes of thermodynamic enhancement of compression are systematically identified as are regimes of radiation-enhancement. The code which incorporates all these effects is used to compute pinch radius ratios in various gases as a measure of compression. Systematic numerical experiments reveal increasing severity in radiation-enhancement of compressions as atomic number increases. The work progresses towards a scaling law for radiative collapse and a generalized specific heat ratio incorporating radiation.